Generation of the Early Cretaceous granitoid in the Dazeshan region, Jiaodong Peninsula: Implications for the crustal reworking in the North China Craton - Dong, Leilei; Yang, Zhiming; Bai, Xin; Deng, Chen (Frontiers in Earth Science, 2023)
Lower crust-derived granitic rocks provide constraints on the crustal reworking process and consequently give hints on the destruction mechanism of the cratons. The North China Craton (NCC) underwent extensive crustal melting in the Mesozoic. This study investigated granitic intrusions in the Dazeshan region of the Jiaodong Peninsula. Whole-rock major and trace element analyses and zircon U-Pb ages coupled with Hf isotopes were used to reveal the crustal reworking processes. Zircons separated from the quartz porphyry, Linglong granite, rhyolite porphyry, and biotite granite showed weighted mean 206Pb-238U ages of 119.2 ± 1.0 Ma, 140.2 ± 1.0 Ma, 120.6 ± 0.5 Ma, and 119.9 ± 0.7 Ma, respectively. The quartz porphyry, rhyolite porphyry, and biotite granite had high silica contents (SiO2 = 74–77 wt.%) but low MgO, Co, and Ni concentrations. The calculated εHf(t) values for the rhyolite porphyry and the biotite granite ranged from −18.3 to −20.0 and −17.8 to −20.2, respectively. These geochemical features imply ancient crust sources. The quartz porphyry showed distinct primitive mantle-normalized rare earth element (REE) patterns and was characterized by lower ΣREE content and lack of pronounced negative Eu anomalies. Whole-rock and zircon Dy/Yb ratios showed no correlation with whole-rock Rb/Sr ratios and zircon Hf contents, reflecting limited effects of crystal fractionation. The Ba/La ratios were also high (>150), but the Sr/Y and La/Yb ratios were low (Sr/Y < 50; La/Yb < 15). These features likely indicate that the quartz porphyry was generated by water-fluxed melting without differentiation. The rhyolite porphyry and biotite granite shared many geochemical similarities, denoting a unified source. The high La/Yb (>30) but low Sr/Y (<20) ratios and apparent negative Eu anomalies indicated plagioclase fractionation. Decreased zircon Dy/Yb with increasing Hf concentrations reflected noticeable amphibole fractionation. These two suites had fairly low Ba/La ratios. These data together point toward an identical source: dehydration melting of a relatively thickened crust. These melts experienced crystal fractionation after extraction. We propose that the intrusions were generated by the underplating of water-rich mafic magma, which provided both fluid and heat and finally induced two kinds of melting.